PENGARUH KEPEMIMPINAN, BEBAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN TETAP DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. SINERGI GULA NUSANTARA PG. ASSEMBAGOES SITUBONDO - Rokhmah, Rika Ainur; Pramesthi, Riska Ayu; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this study is to find out the impact of leadership, workload and organizational culture on the performance of employees with continuous job satisfaction as a variable intervening on PT. Sinergi Gula Nusantara PG. Assembagoes Situbondo. Population on this study are Employees Permanent PT. Simple probability sampling is a method of sample-taking without considering the population in this study. Data analysis and hypothesis testing in research using Structural-partial equation model Least square (PLS-SEM). The results of the hypothesis test of its impact directly using the PLS 3.2.8 smart application, Showing that leadership has a significant positive impact on job satisfaction, workload has a substantial positive effect on employment satisfaction and organizational culture has a major positive influence on work satisfaction. Leadership has a positive but non-significant impact on Performance, Workload has a significant positive impact on performance, and Organizational culture has a substantial positive effect on Performance. Job satisfaction has a positive but non-significant impact on performance. Leadership has a positive but non-significant influence on Performance through Job Satisfaction, Workload positively but does not significantly influence performance through job satisfaction, and Organizational culture positively but does not significantly affect performance through employment satisfaction.